A meso-scale study of unusually heavy rainfall satellite over south Kerala - GUPTA, G. R. (MAUSAM, 1990)
On 17-18 October 1964 unusually heavy rainfall (40.10 cm) occurred in association with a thunderstorm at Trivandrum in Kerala State. A meso-scale study of the rainfall is attempted which shows a small vortex traveling across Trivandrum on the night of 17October and causing unusually heavy rainfall. The orography might have further accentuated the situation at Ponmudi where 40.64 cm rainfall at a distance of 10 km occurred. Thus, existence of a low level meso-scale vortex & sudden strengthening of winds in upper troposphere provided favorable conditions for development of severe thunderstorm activity over Trivandrum. Region of maximum rainfall followed the track of this vortex.